Improving assessment of groundwater-resource sustainability with deterministic modelling: a case study of the semi-arid Musi sub-basin, South India - Massuel, S.; George, B.A.; Venot, Jean-Philippe; Bharati, Luna; Acharya, S. (2013)
Since the 1990s, Indian farmers, supported by the government, have partially shifted from surface-water to groundwater irrigation in response to the uncertainty in surface-water availability. Water-management authorities only slowly began to consider sustainable use of groundwater resources as a prime concern. Now, a reliable integration of groundwater resources for water-allocation planning is needed to prevent aquifer overexploitation. Within the 11,000-km2 Musi River sub-basin (South India), human interventions have dramatically impacted the hard-rock aquifers, with a water-table drop of 0.18m/a over the period 1989-2004. A fully distributed numerical groundwater model was successfully implemented at catchment scale. The model allowed two distinct conceptualizations of groundwater availability to be quantified: one that was linked to easily quantified fluxes, and one that was more expressive of long-term sustainability by taking account of all sources and sinks. Simulations showed that the latter implied 13% less available groundwater for exploitation than did the former. In turn, this has major implications for the existing waterallocation modelling framework used to guide decision makers and water-resources managers worldwide.